Virtopsy as a Revolutionary Tool for Cetacean Stranding Programs: Implementation and Management - Tsui, Henry C. L.; Kot, Brian C. W.; Chung, Tabris Y. T.; Chan, Derek K. P. (Frontiers in Marine Science, 2020)
On top of conventional necropsy, virtopsy (postmortem computed tomography and postmortem magnetic resonance imaging) has been integrated into the Cetacean Stranding Response Programme in Hong Kong since March 2014. To date, 177 out of 240 local stranded cetaceans have been examined by virtopsy. This integration has modernised the characterisation and documentation of cetacean biological health profiles and causes of death. During this 6-year period, critical pitfalls regarding logistics, carcass recovery, handling, and preservation have been identified. A strategic management scheme is crucial for the successful incorporation of virtopsy into this pioneer programme. This study explains the workflow of the Cetacean Virtopsy Stranding Response Programme in Hong Kong waters. Difficulties encountered are highlighted and practical solutions to address management issues are proposed to consolidate the stranding response network.